Hubungan Kebisingan dan Beban Kerja Fisik Dengan Kualitas Tidur Pada Pekerja Bagian Tenun di CV. X - Rizal Pratama Nugraha; Ratna Fajariani; Bachtiar Chahyadhi (Sekolah Vokasi, Universitas Sebelas Maret, 2022)
Sleep is a basic need for every human being. Everyone can not be separated from sleep, where a person's condition depends on the quality of sleep. Sleep, which is directly related to health and quality of life, is a basic need for humans to continue their bio-psycho-social and cultural functions. Sleep quality can be affected by the noise and also physical workload. This study aims to determine the relationship between noise and physical workload with sleep quality on weavers at CV. X. This research is an analytic observational study, with a cross sectional approach. This research using total sampling technique with total 40 workers in the weaving section of CV. X. The research instrument used is a sound level meter to measure noise, pulseoxymeter to measure physical workload, and PSQI questionnaire Tools to measure sleep quality. The data analysis technique used spearmen's-rho, somers'd, and binary logistic regression. Spearman’s-rho test results showed that there was a significant correlation between noise and sleep quality (p=0,010), direction of correlation positive, and correlation coefficient medium (ρ=0,404). Somers’d test result showed that there was a significant correlation between physical workload and work sleep quality (p=0,000), direction of correlation positive, and correlation coefficient medium (dyx=0,466). Multivariate test results show that variable that most influences the sleep quality variable is physical workload variable (OR=22,276). There is a significant correlation between noise and physical workload with sleep quality on the weavers at CV. X.